Development of the "JATARA" Board Game as a Cultural Exploration Medium for IPAS in Grade IV Elementary School - Maharani Maharani; Siti Istiningsih; Aisa Nikmah Rahmatih (Journal of General Education and Humanities, 2025)
Lack of learning media innovation is making students less active and leading to a low understanding of student concepts related to the material IPAS. This study aims to develop a board game exploring the Indonesian culture "JATARA", which is appropriate and effective as a cultural exploration medium for grade IV elementary school. The novelty of this study lies in the larger physical game board and the guidebook equipped with modules and handouts of material about Indonesian culture. This study uses the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects were grade IV students of Lamenta State Elementary School. The data collection techniques used were questionnaires and tests. The research findings revealed that: (1) expert validation produced an average score of 91.25%, categorized as "very appropriate"; (2) material expert validation produced a score of 87.5%, categorized as "very appropriate"; (3) small group trials conducted by teachers and students produced scores of 97.92% and 95.83% respectively, both categorized as "very appropriate"; (4) large group trials produced a score of 96%, also categorized as "very practical"; (5) The evaluation test results were 100% in the "very effective" category. These results indicate that JATARA media is suitable and effective for use as a cultural exploration medium for grade IV elementary school. This media contributes significantly to "IPAS" learning by offering practical and innovative solutions that can increase student involvement and understanding in a cultural context, at the elementary education level.